2022
DOI: 10.1002/lary.30449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serial Intralesional Steroid Injections on Idiopathic Subglottic Stenosis

Abstract: ObjectivesSerial intralesional steroid injection (SILSI) has been increasingly used to treat idiopathic subglottic stenosis (iSGS). Prior studies have shown effectiveness, but not in all patients. This multi‐institutional study evaluates the effect of SILSI on time to recurrent operation, peak expiratory flow (PEF), and dyspnea.MethodsPost‐hoc secondary analysis of the North American Airway Collaborative data were performed to evaluate the outcomes of iSGS patients undergoing and not undergoing SILSI. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…27 Lastly, not all patients appear to benefit from SILSI and a recent multi-institutional study did not show a comparative benefit for heterogeneously implemented SILSI on time to recurrence, peak expiratory flow, or clinical COPD questionnaire scores. 17 Accordingly, identifying which patients are most likely to benefit is desirable. In our dataset, 2 measures reflecting pre-SILSI disease severity (number of operations prior to SILSI and most recent inter-operative interval) predicted higher likelihood of needing additional procedures after starting SILSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Lastly, not all patients appear to benefit from SILSI and a recent multi-institutional study did not show a comparative benefit for heterogeneously implemented SILSI on time to recurrence, peak expiratory flow, or clinical COPD questionnaire scores. 17 Accordingly, identifying which patients are most likely to benefit is desirable. In our dataset, 2 measures reflecting pre-SILSI disease severity (number of operations prior to SILSI and most recent inter-operative interval) predicted higher likelihood of needing additional procedures after starting SILSI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent multi-institutional study did not show significant benefit for adding SILSI after endoscopic dilation for time to recurrent operation, peak expiratory flow, or clinical COPD questionnaire score. 17 Of note, that multi-institutional study did not employ a uniform SILSI protocol and steroid injections began a median of 1 year after dilation. Naunheim et al reported the largest single institution cohort of 55 patients with average follow-up of 3.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the 52 patients who underwent serial intralesional steroid injection to the 238 patients of similar stenosis who did not, they ultimately found no difference in time to recurrence, need for secondary procedure, or dyspnea scores. 29 It is currently unclear if pregnant women would benefit from this procedure more than non-pregnant persons.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Surgery is the primary treatment for LTS, but numerous adjuvant and neoadjuvant medical therapies exist, including corticosteroid injections, inhaled corticosteroids, mitomycin C application, antibiotics, and proton pump inhibitors 9 . Serial intralesional steroid injections (SILSIs) are an increasingly popular adjuvant medical option for LTS 10,11 . Surgical treatment options are either endoscopic or open procedures.…”
Section: Introductionmentioning
confidence: 99%